Molecular detection of reproductive symbionts and parthenogenesis experiments in Tuta absoluta from Argentina: facing potential for sustainable and specific pest control strategies - Cagnotti, Cynthia Lorena; Conte, Claudia Alejandra; Kramar, Jacqueline; Lanzavecchia, Silvia Beatriz; Lopez, Silvia Noemi (Wiley, 2023)
Tomato leafminer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a key pest of tomato crops. Specific and environmentally friendly control strategies against this pest, such as the sterile insect technique (SIT), are under development and sexual reproduction has emerged as a key focal point to ensure its success. In the present study, we analyzed four representative T. absoluta populations from Argentina, focusing on the molecular detection of endosymbionts potentially associated with reproductive abnormalities and on determining whether parthenogenesis can occur under laboratory conditions. Larvae of T. absoluta were collected in commercial tomato plantations from La Plata and Mar del Plata (both in Buenos Aires province), Bella Vista (Corrientes province), and Yuto (Jujuy province). Tuta absoluta adults were evaluated by standard PCR for the presence of reproductive endosymbionts (Wolbachia sp., Spiroplasma sp., Arsenophonus sp., Cardinium sp., and Rickettsia sp.). For parthenogenesis assays, 20–23 virgin females from each T. absoluta geographic population were life-long isolated in Petri dishes with a tomato leaf. Fecundity, fertility, and female longevity were estimated and compared with results from mated females from each population. Our results showed the presence of a unique endosymbiont (Wolbachia sp. supergroup B, sequence type 41). Fecundity of the unmated females was significantly lower than fecundity of mated females in all T. absoluta populations. In addition, unmated females only laid infertile eggs. In conclusion, the absence of parthenogenesis in T. absoluta from representative geographic populations supports the implementation of SIT and mating disruption as effective control strategies against this pest in Argentina.